Presidents - Csink, Lóránt (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Comparing heads of states theoretically is a rather difficult task.1 The comparative method is useful only if the institutions set together are comparable. In general, several institutional solutions exist for the status and competences of heads of states; nevertheless, there is a significant difference between the queen (or king) of the United Kingdom, the president of the United States and the German federal president, even though they all function as head of states. This chapter focuses on the presidents of Central Eastern Europe. Firstly, it examines the role of presidents of the region; secondly, it analyses the ways of elections; thirdly, it addresses the competences of the presidents; and finally, it deals with the termination of office. This chapter does not deal with the crucial question of the extent to which the president is involved in daily politics or how they affect governance; this issue, which concerns the form of government, is the topic of a separate chapter. However, the form of government is inseparable from the president, and this chapter necessarily reflects on the president’s role in state power. KEYWORDS: election of presidents, competences of presidents, parliamentarism, separation of powers.